Pengaruh Nilai dan Ukuran Perusahaan terhadap Tax Avoidance dengan Profitabilitas sebagai Moderasi pada Perusahaan Pertambangan BEI 2019–2023 - Erny Susanty; Tiolina Evi Nausta Pardede (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the influence of firm value and firm size on tax avoidance, with profitability as a moderating factor, focusing on mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The background of this research lies in Indonesia’s relatively low tax ratio compared to neighboring countries, which raises concerns about the potential for tax avoidance within the mining industry, a sector that significantly contributes to state revenue. Using a quantitative causal approach, the study employs a balanced panel dataset of 75 firm-years from 15 purposively selected companies. The independent variables are firm value (Tobin’s Q) and firm size (logarithm of total assets), with tax avoidance (effective tax rate) as the dependent variable and profitability (return on assets) as the moderating variable. Data were analyzed through descriptive statistics, followed by panel regression tests (Chow, Hausman, and Lagrange Multiplier) to select the appropriate model, and then Moderated Regression Analysis (MRA) to evaluate profitability’s moderating role. The findings reveal that both firm value and firm size have a positive and significant effect on tax avoidance, indicating that larger and more valuable firms tend to practice efficient tax planning. However, profitability does not moderate these relationships. The study concludes that long-term value and resources, rather than profit levels, drive tax avoidance behavior and recommends risk-based supervision for large, high-value firms.